2016
DOI: 10.1016/j.jspr.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and application rate on efficacy of a diatomaceous earth formulation against Tribolium castaneum adults

Abstract: Unsanitary storage bins can harbor grain-infesting insects, including the red flour beetle, Tribolium castaneum (Herbst). In a previous study involving heat treatment of empty bins, temperatures in the range of 50-55C for 2-4 h were effective in completely killing storedproduct insects. Previous research in flour mills showed improved efficacy in killing storedproduct insects by using diatomaceous earth (DE) dusts at temperatures below 50°C. In the current study, the efficacy of a diatomaceous earth formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…When evaluating the effect of three corn grain storage temperatures (15, 25 and 30°C) submitted to three doses of DE (500, 750 and 1000 g t -1 ), Ceruti et al (2008) observed that the higher the dose and the temperature, higher the mortality, corroborating with the results obtained in the present study. Likewise, Frederick and Subramanyam (2016) found higher mortality rate of Tribolium castaneum, Herbst, 1797 (Coleoptera: Tenebrionidae) adults when the grains treated with DE were stored at higher temperatures.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…When evaluating the effect of three corn grain storage temperatures (15, 25 and 30°C) submitted to three doses of DE (500, 750 and 1000 g t -1 ), Ceruti et al (2008) observed that the higher the dose and the temperature, higher the mortality, corroborating with the results obtained in the present study. Likewise, Frederick and Subramanyam (2016) found higher mortality rate of Tribolium castaneum, Herbst, 1797 (Coleoptera: Tenebrionidae) adults when the grains treated with DE were stored at higher temperatures.…”
Section: Resultsmentioning
confidence: 89%
“…In recent years several studies evaluating the effect of DE on the control of insect pests of stored grains have been published, highlighting its potential as a protective agent for stored grains (FREDERICK;SUBRAMANYAM, 2016;JAIROCE et al, 2016;WAKIL and SCHMITT, 2015;KAVALLIERATOS et al, 2015;ZIAEE et al, 2014;EISSA et al, 2014;ATHANASSIOU et al, 2014;NWAUBANI et al, 2014;DOUMBIA et al, 2014). However, the studies are largely dedicated to the evaluation of doses and sources, with few studies evaluating the efficacy of DE at different storage temperatures and its residual effect (long-term storage), especially for the protection of stored corn grains against S. zeamais, associating its influence on the quantitative parameters of the grains.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the increase in the moisture content of the treated commodities has a notable positive effect on the disinfestation using dielectric heating methods of radiofrequency, infrared, and microwave treatments (Jiang et al., 2019; Pan et al., 2008; Vadivambal et al., 2008). The investigations on the pesticidal efficacy of spinosad (Athanassiou et al., 2008) and diatomaceous earth (Frederick & Subramanyam, 2016) have reported that the changes in factors such as temperature and relative humidity affect the insect mortality and the impact varies depending on the insect species. Mcneil (1991) reviewed that factors such as temperature, relative humidity, day length, light intensity, wind speed, and atmospheric conditions affect the emission and reception of pheromones.…”
Section: Role Of Climatic Change On Stored Grain Pests and Control Mementioning
confidence: 99%
“…Moreover, higher temperatures usually increase insect movement inside the grains, causing increased contact with the diatomaceous earth and, consequently, greater cuticular damage. Furthermore, it is important to feature that unlike synthetic insecticides, DE is inert and does not degrade with the increase of temperature, which allow farmers to use DE products combined with elevated temperatures (Dowdy, 1999;Fields and Korunic, 2000;Athanassiou et al, 2005;Athanassiou et al, 2011;Bohinc et al, 2013;Frederick and Subramanyam 2016). Values in the same row followed by different lowercase letter are significantly different when exposed to different temperatures; Similar capital letters on the same column indicate no significant differences between treatments (Duncan's multiple range (P < 0.05; df (4,14) ) was 19.36 for columns and rows).…”
Section: Source Of Variationmentioning
confidence: 99%